2013
DOI: 10.5586/aa.1986.011
|View full text |Cite
|
Sign up to set email alerts
|

Content of basic macroelements in common parasitical weeds

Abstract: The content of N, P2O5, K2O, CaO and MgO was measured in parasitical weeds, as well as in their host plants and in the soil. The soil was also analyzed for its humus content and pH. The statistical analysis of the results justified the ascertation that, on the average, weeds were richer in macroelements then their host plants. In the investigated two groups of plants, both differences as well as similarities in the usage of the mentioned components were found, and the component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…This may be the main reason why the content of some mineral nutrients is higher in mistletoe leaves than in infested and non-infested oak trees. Many other authors have reported similar findings on various host and mistletoe species [89][90][91] Mistletoe parasitism is a strategy for N acquisition [61,88]. In our study, the N content was markedly lower in mistletoe than in both infested and non-infested oaks.…”
Section: Relationships Between Oaks and Mistletoes: Growth And Minera...supporting
confidence: 85%
“…This may be the main reason why the content of some mineral nutrients is higher in mistletoe leaves than in infested and non-infested oak trees. Many other authors have reported similar findings on various host and mistletoe species [89][90][91] Mistletoe parasitism is a strategy for N acquisition [61,88]. In our study, the N content was markedly lower in mistletoe than in both infested and non-infested oaks.…”
Section: Relationships Between Oaks and Mistletoes: Growth And Minera...supporting
confidence: 85%
“…manteve o efeito da infecção primária, constatando-se assim a ação dos diferentes parasitas sobre o mesmo hospedeiro, comprovando respostas à infecção. Malicki & Berbeciowa (1986) Cuscuta spp. em petúnia hfürida, os níveis de proteína e fósforo sofreram redução na planta hospedeira pela primeira infecção por Orobanche spp., mantendo-se assim durante a segunda infecção por Cuscuta spp.…”
Section: Cuscuta Racemosaunclassified